Radioligand Therapy with [177Lu]Lu-DOTA-TATE or [177Lu]Lu-DOTA-TATE and [90Y]Y-DOTA-TATE in Patients with Neuroendocrine Neoplasms of Unknown Locations, or Locations Other Than the Midgut and Pancreas as Primaries in a G1, G2 and G3 Grade - Adam Daniel Durma; Marek Saracyn; Maciej Kołodziej; Katarzyna Jóźwik-Plebanek; Beata Dmochowska; Adrianna Mróz; Wawrzyniec Żmudzki; Grzegorz Kamiński (MDPI AG, 2023)
Background: Neuroendocrine neoplasms (NENs) are a rare group of tumors with a different clinical course, prognosis and location. Radioligand therapy (RLT) can be used as a first or second line of treatment. It is registered in gastroenteropancreatic NENs (GEP-NENs) as grades G1 and G2. Tumors with an unknown point of origin, diagnosed outside the gastrointestinal tract and pancreas (non-GEP) or at the G3 grade, remain in the "grey area" of treatment. Materials and Methods: Analysis of 51 patients with NENs who underwent RLT in a single highest reference center from 2018 to 2023 was performed. Treatment was administrated to the patients with neoplasms of unknown origin, non-GEP-NENs, and ones with G3 grade. In total, 35 patients received 177-Lutetium (7.4 GBq), while 16 received 177-Lutetium and 90-Yttrium with equal activities (1.85 + 1.85 GBq). Results: The progression-free survival (PFS) before RLT qualification was 34.39 ± 35.88 months for the whole study group. In subgroups of patients with an unknown tumor location (n = 25), the median PFS was 19 months (IQR = 23), with "other" locations (n = 21) at 31 months (IQR = 28), and with NEN G3 (n = 7) at 18 months (IQR = 40). After RLT, disease stabilization or regression was observed in 42 (87.5% of) patients. RLT did not cause statistical changes in creatinine or GFR values. Hematological parameters (RBC, WBC, PLT, HGB) as well as chromogranin A concentration decreased significantly. There were no statistical differences between both subgroups regarding the type of radioisotope (177-Lutetium vs. 177-Lutetium and 90-Yttrium). After RLT in long-term observation, the median observation time (OT) was 14 months (IQR = 18 months). In patients with progression (n = 8), the median PFS was 20 months (IQR = 16 months), while in patients with confirmed death (n = 9), the median overall survival (OS) was 8 months (IQR = 14 months). Conclusions: Our study showed that 87.5% of NEN patients with unknown origin, non-GEP-NENs, and those with GEP-NEN G3 grade had benefited from the radioligand therapy. There were no significantly negative impacts on renal parameters. The decrease of bone marrow parameters was acceptable in relation to beneficial disease course. The decrease of chromogranin concentration was confirmed as a predictive factor for disease stabilization or regression.